Beyond artificial intelligence: why companies need to go the extra step. Issue 1 (24th October 2018) - Lichtenthaler, Ulrich
Abstract : Purpose: The purpose of this paper is to underscore the need for developing a meta-intelligence in companies based on a conceptual framework for combining artificial and human intelligence. Design/methodology/approach: This is a conceptual paper, which draws on the insights from extant theoretical and empirical research. Findings: In light of a growing trend towards artificial intelligence (AI), most companies face substantial difficulties, which often derive from an excessive emphasis on merely replacing human intelligence by means of AI. To capture the complementary benefits of artificial and human intelligence beyond mere cost savings, firms do not only need to enhance their advanced analytics while continuing to develop their human intelligence. Rather, they additionally need a meta-intelligence for transforming their intelligence architecture in line with corporate strategy. Consequently, the firms need intelligence 3 – comprising AI, human intelligence and the meta-intelligence. Originality/value: The new concept of a meta-intelligence for renewing and recombining artificial and human intelligence helps to reconcile diverse findings in prior research. Without this meta-intelligence, most AI initiatives will be isolated endeavors, which may have positive effects but likely will not live up to the expectations.